Relevant factors to take in consideration when applying a collaborative consumption practice in Peru - Villavicencio Rodríguez, Giovanna (2020)
Have you ever though on sharing your belongings in order to gain an extra income? Today this is possible thanks to the creation of several digital platforms that allows people to connect in order to obtain what they need. This new phenomenon is known as collaborative consumption and it’s a reality that is changing the way people behave. The term collaborative consumption is defined as an environment where the act of buying and distributing goods or services is made by stablishing a fee or another type of compensation. This practice has three main actors: the digital platform provider, the person who provides the service and the customer, and it’s characterized mainly because it works by the means of the internet. This report explores and defines what could be the potential results when implementing a collaborative consumption practice in Lima-Peru. For this, an exploratory research was conducted in order to stablish which were the main factors to take in consideration when applying this type of practice in the country. Moreover, the study analyzes the information associated with this practice by taking in consideration relevant factors such as the economical, political, social and technological situation of the country in terms of their population insights.